Die Entwicklung der Innenstadt von Budapest zwischen City- und Slumbildung - Lichtenberger, Elisabeth (ERDKUNDE, 1995)
In the mid-1980s the present author started research into urban decay and urban renewal in Vienna and in Budapest against the general background of a comparison of political systems. The findings on Vienna were published. Now, those with respect to Budapest can be presented. Budapest’ s urban renewal area coincides with the inner city of the Founders’ Period east of the Danube and comprises the districts V to IX. It covers an area of 2644 hectares with 6628 buildings housing approximately 350,000 persons, and about half of them live in blocks of flats showing considerable decay. The analysis of the present spatial pattern of decay and renewal resulted in the finding that urban renewal in Budapest must be seen as a dual system bound up with that of economy: there is a first, public/official institution which contains a second, informal system active in categories of a protomarket. The rapid take-off of the tertiary and quaternary sectors after the political changes can only be explained with reference to this second, informal system of urban redevelopment. As the general framework underwent changes in the phase of transition an analysis of commercialized urban renewal in connection with the real estate market for office space and - in accordance with the theory of polarization normative statements with regard to possible solutions of the slum problem seem to be called for. Within a very short time, immediately after the political changes, the internationalization of the real estate market made itself felt in Budapest. Both foreign concerns and Hungarian enterprises triggered a boom in the construction of office buildings. On the other hand, there are slums within walking distance of the CBD. Two slum areas are to be distinguished, on the one hand the areas of badly equipped tiny flats dating from the Founders’ Period that had already been slums in the inter-war period, and on the other hand areas in which decay had only set in in the post-war era after the original inhabitants had been expelled and replaced by other groups during World War 11 and in the ensuing years. The transition from egalitarian societal structures to a new class society, by means of the creation of wealth, has enhanced the existence of a central poverty as far as the incomes are concerned. A central social crater with all sorts of desorganization phenomena is beginning to develop, separated from the CBD by only a narrow zone.